A group support system process for the definition of software requirements. (28th December 2009) - Hannola, Lea; Elfvengren, Kalle; Tuominen, Markku
The definition of software requirements in the early phases of the software innovation process is considered to be an extremely important and challenging task, as decisions about precisely what will be developed are made during this stage. This paper presents a Group Support System (GSS) process for the definition of software requirements, and studies the usability of a GSS as a tool for requirements definition. The developed process was validated in a telecommunications company, and the study shows that requirements definition was expedited and more effective with the GSS-supported process compared to the traditional methods used in the case company.